Delinquent-Prone Communities. - Weatherburn, Donald James (Cambridge criminology series., 2000)
Despite a century of effort, criminologists do not yet fully understand the relationship between disadvantage and crime. This book challenges the conventional view that disadvantage causes crime because it motivates people to offend, and argues instead that disadvantage causes crime because it disrupts the parenting process.